Towards a "fourth 90": A population-based analysis of post-tuberculosis pulmonary function testing in British Columbia, Canada, 1985–2015. Issue 2 (13th August 2020) - Basham, C. Andrew; Cook, Victoria J.; Johnston, James C.
Mounting evidence of chronic obstructive and restrictive lung disease among respiratory tuberculosis (TB) patients after treatment [1–4] raises questions about current practice in terms of linkage to care once pharmacologic treatment for TB has stopped. A systematic review of post-TB COPD showed pooled odds ratio of 3.05 (95% CI 2.42–3.85) for people with a history of TB compared to non-TB controls [3]. Another review reported a range of proportions of TB patients with airflow obstruction post-TB of 0.18–0.87 [1]. The development of a "fourth 90", in addition to the three objectives of the Stop TB Partnership's Global Plan to End TB, has been suggested: "Ensuring that 90% of all people successfully completing treatment for TB can have a good health-related quality of life" [5]. Post-tuberculosis lung disease is a growing concern globally. In a Canadian sample, only 3% of respiratory TB cases underwent pulmonary function testing within 90 days of treatment end. Benchmarks for post-TB pulmonary function testing are needed. https://bit.ly/2WX3tVf